2012
DOI: 10.1007/s11999-012-2259-x
|View full text |Cite
|
Sign up to set email alerts
|

Has Diversity Increased in Orthopaedic Residency Programs since 1995?

Abstract: Despite the increase in diversity in the orthopaedic workforce during the past 15 years, ethnic and gender disparities persist among orthopaedic residency programs regarding residents, clinical faculty, and basic research faculty. To increase diversity in orthopaedic residency programs, an emphasis on recruiting ethnic and gender minority candidates needs to become a priority in the orthopaedic academic community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 4 publications
3
24
0
Order By: Relevance
“…This study has a number of limitations; first, it was a survey-based study with an overall response rate of 48.4%, which could result in survey sampling bias, tending to systematically overestimate or underestimate population parameters. However our response rate is within the norm of the similar published literature 26 - 30 . Additionally, the survey has not been validated.…”
Section: Discussionsupporting
confidence: 86%
“…This study has a number of limitations; first, it was a survey-based study with an overall response rate of 48.4%, which could result in survey sampling bias, tending to systematically overestimate or underestimate population parameters. However our response rate is within the norm of the similar published literature 26 - 30 . Additionally, the survey has not been validated.…”
Section: Discussionsupporting
confidence: 86%
“…13 However, the effect of these efforts within the ACGME, American Academy of Orthopaedic Surgeons, and on the medical school level remains to be seen in the years to come. Although it has been shown that over the last decades, the diversity in orthopaedic residency programs has increased, 14 our study is in line with previous reports, indicating that women and minorities remain underrepresented in orthopaedic residencies. 345,78,9,1011 Future efforts should target increasing the acceptance of women and minorities in orthopaedic residency programs during the residency match and interview process.…”
Section: Discussionsupporting
confidence: 92%
“…First, the relatively low number of URMs in medical school has previously been suggested as a potential reason for low numbers in residency programs 2 . However, the current study shows that the number of URM orthopaedic surgery applicants is relatively proportional to the number of URM medical students, which suggests that there may be a barrier at the residency selection level.…”
Section: Discussionmentioning
confidence: 99%